Regional flood frequency analysis using L-moments for North Karoon basin, Iran - Borujeni, Sattar Chavoshi; Sulaiman, Wan Nor Azmin; Eslamian, Saeid (Serials Publications, 2010)
L-moment theory is increasingly being used in hydrology of floods for regional frequency analysis. The L-moments have been used for parameter estimation, homogeneity testing and selection of the regional distribution. Records of peak floods, observed in North-Karoon basin, are analyzed using five distributions: generalized logistic, generalized extreme value, lognormal, Pearson type III and generalized Pareto. Each of these three-parameters distributions are estimated by the L-moment method. The discordancy index and homogeneity testing show that 5 out of the 7 study sites belong to a homogenous region. Based on the L-moment ratios diagram and the goodness-of-fit measure, the three-parameter lognormal distribution is identified as the most appropriate distribution in the homogeneous study region. The regional peak flood estimates for each return period are obtained based on this distribution.